REVIEW OF THE EUROPEAN EXPERIENCE OF AIC DEVELOPMENT AND THE ROLE OF GREEN TECHNOLOGIES IN THE MODERNISATION OF THIS PROCESS - Іnna Honcharuk; Dina Tokarchuk (Baltic Journal of Economic Studies)
The relevance of the study is due to the need to adapt the agro-industrial complex (AIC) to modern challenges, in particular environmental and economic, to ensure its sustainable development. Studying the European experience of AIC development and the introduction of green technologies opens up opportunities for modernising the industry and increasing its efficiency in the face of global change. The purpose of the study is to examine the experience of European countries in the development of the AIC, to identify the main trends and to determine the place of green technologies in the modernisation of production. The object of the study is the agro-industrial complex of European countries, as well as the processes of modernisation of this sector, which are taking place through the introduction of modern green technologies, innovative practices, as well as the adaptation of European approaches to ensuring sustainable and efficient development of the agricultural sector in the face of global challenges and environmental constraints. The research methodology is based on systemic, comparative and analytical approaches that provide a comprehensive analysis of the agro-industrial complex in the context of its modernisation. The theoretical framework includes: a systemic approach that considers the agro-industrial complex as an integral interconnected system operating in an economic, social and environmental environment; a comparative method that provides an analysis of the European experience in implementing green technologies, with an emphasis on adapting these approaches to other conditions, identifying best practices and assessing the possibilities of their application for the modernisation of the industry; an environmental approach that studies the impact of implementing green technologies to reduce the negative impact of agricultural activities on the environment. The analysis of the main characteristics of EU agriculture in 2019-2023 showed that labour productivity in the sector is growing annually, while real factor income varies by year. The growth of agricultural production along with a decrease in CO2 emissions indicates the application of environmental measures, however, the share of the industry in the total European emissions is growing, which confirms the need for its modernisation on a green basis. The authors systematise the main areas of green technologies in the AIC. The study showed that EU countries are actively implementing various effective models of green business in the agricultural sector, with the mainstream being the creation of green clusters, the development of green energy and the production of organic products. The study of the development of green energy in the European AIC has identified biogas and biomethane production as the fastest growing sectors; countries such as Denmark and Sweden have already replaced more than 25% of natural gas consumption in 2022. The analysis of the development of organic production showed an increase in the area under organic production (by 5.7% annually in 2012-2020) and an increase in the volume of organic production. Based on the study of EU programmes and initiatives related to the use of green technologies in the agricultural sector, the article summarises that they are aimed at reducing greenhouse gas emissions, developing organic production, increasing the efficiency of natural resources use, expanding the production and use of renewable energy sources in the agricultural sector, preserving biodiversity and introducing innovations for sustainable agricultural development. The analysis of the CAP 2023-2027 showed an intensification of the environmental direction of the industry's development to comply with the European Green Deal. Thus, green technologies are becoming an integral part of the development of the AIC in European countries and their use is being stimulated through financial instruments and regulatory frameworks.